Troubleshooting bei Patienten mit Herzschrittmacher und ICD - Meyer zu Vilsendorf, Dorothee; Hansky, Bert; Baumann, Philipp; Stellbrink, Christoph (DMW - Deutsche Medizinische Wochenschrift, 2018)
Because of the growing number of implanted cardiac pacemakers and defibrillators and the ever-increasing complexity of these devices a fundamental knowledge of device malfunctions is of utmost importance even for the non-cardiology physician. Apart from hardware problems such as device infection, lead fracture or dislocation, basic knowledge of the pacemaker sensing and pacing algorithms is also necessary in order to judge the stimulation behavior in different clinical settings. With this respect, there are specific problems for antibradycardia and resynchronizing pacemakers as well as implantable defibrillators. This article gives an overview of the most common problems with cardiac pacemakers and defibrillators as well as the differential diagnostic and therapeutic management for the physician without specific training in arrhythmology.
Keywords: Herzschrittmacher; implantierbarer Defibrillator; Infektion; Tachykardie; Bradykardie